Uji Aktivitas Antibakteri Fraksi n-Heksan, Etil Asetat, dan Air Ekstrak Daun Jambu Air (Syzygium aqueum) terhadap Bakteri Staphylococcus epidermidis ATCC 12238 - Adhe Wibawa Mahardika Putra; Tatiana Siska Wardani; Anna Fitriawati (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
This study aimed to evaluate the antibacterial activity of water apple (Syzygium aqueum) leaf extract against Staphylococcus epidermidis. The leaves were collected from Pranan Village, Sukoharjo District. After proper botanical identification (determination) at B2P2TOOT Karanganyar, the leaves were dried, ground into simplicia powder, and extracted using 70% ethanol through maceration. The ethanol extract was then fractionated based on solvent polarity using n-hexane (nonpolar), ethyl acetate (semipolar), and water (polar). Antibacterial testing was conducted using various concentrations (25%, 12.5%, 6.25%, 3.125%, and 1.565%), with clindamycin as a positive control and DMSO as a negative control. The study assessed antibacterial effectiveness through inhibition zone measurements, Minimum Inhibitory Concentration (MIC), and Minimum Bactericidal Concentration (MBC). Results demonstrated that both the ethanol extract and ethyl acetate fraction exhibited antibacterial activity against Staphylococcus epidermidis. The 25% concentration of the ethyl acetate fraction produced the largest inhibition zone (27.57 mm), followed by the ethanol extract (21.53 mm). Both the ethanol extract and the most active fraction showed MIC values of 1.565%, with the MBC of the ethyl acetate fraction also at 1.565%. These findings suggest that water apple leaves possess promising antibacterial properties, especially in the ethyl acetate fraction, against Staphylococcus epidermidis.leaves (Syzygium aqueum) against the growth of Staphylococcus epidermidis ATCC 12238.